Analisis Perbandingan Metode Fingerprinting dan Dead Reckoning Pada Sistem Penentuan Posisi Dalam Ruangan - Rolly Junius Lontaan; Oktoverano Lengkong; Jacquline Waworundeng (TeIKa, 2023)
Indoor positioning system technology is one of the solutions to problems that cannot be done by positioning technology for objects determined by the Global Positioning System (GPS) when the position is in a multi-storey building. To determine the position in the room, there are several methods, including the fingerprinting method and the dead reckoning method, which are methods that will be analyzed in comparison between the two methods by testing their performance or accuracy, the advantages and disadvantages of each method and providing recommendations for the use of the appropriate method. appropriate in certain situations. Where Fingerprinting is more accurate in situations with lots of obstructions and high signal density, while dead reckoning is more suitable for use in situations with lots of movement and few obstructions.